Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $f_x = \mathrm{Pr}\{X = x\}$ be a probability mass function. The cumulative distribution function of $X$ is then defined as $F_x = \mathrm{Pr}\{X \le x\} = \sum_{z=0}^{x} f_z$.

Therefore, the probability mass function can be written in terms of the cumulative distribution function as $f_x = F_x - F_{x-1} ~\forall x \in \mathbb{N}$.

The expected value of $X$ is also defined as $\mathbb{E}[X] = \sum_{x=1}^{\infty} x \, f_x$. Expanding this equation using the previous statements, we get:

$$\begin{align} \mathbb{E}[X] & = \sum_{x=1}^\infty x \cdot ( F_x - F_{x-1} ) \\ & = \sum_{x=1}^\infty x \, F_x - \sum_{x=1}^{\infty} x \, F_{x-1} \\ & = \sum_{x=1}^\infty x \, F_x - \sum_{x=1}^{\infty} (x-1) \, F_{x-1} - \sum_{x=1}^\infty F_{x-1} \\ & = \sum_{x=1}^\infty x \, F_x - \sum_{x=0}^{\infty} x \, F_x - \sum_{x=0}^\infty F_x \\ & = \sum_{x=1}^\infty x \, F_x - \sum_{x=1}^{\infty} x \, F_x - \sum_{x=0}^\infty F_x \\ & = -\sum_{x=0}^\infty F_x. \end{align} $$

The last term is the negative of sum of non-negative terms and thus, is negative. Therefore, it turns out that the expected value of random variable $X \ge 0$ is negative, that is a contradiction. Just wondering which of the derivations above is the source of the problem?

share|cite|improve this question
up vote 6 down vote accepted

Note that $\sum xF_x$ and $\sum xF_{x-1}$ are divergent series. As soon as you introduce them into the mix, all hope is lost.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.